USING VIDEO LEARNING TO IMPROVE STUDENTS’ MATHEMATICAL ABILITY - Shiwei Tan; Lingjie Zou; Tommy Tanu Wijaya (Mahesa Research Center, 2020)
In some traditional large-class classrooms, there are problems such as inactive teaching process and poor teaching pertinence, which makes some students who are easily distracted and have the poor receptive ability cannot keep up with the teaching progress and gradually become students with learning difficulties. This research method using pretest-posttest control group design. The sample of this research is the experimental class method there are 48 students and in the control class 48 students grade 7 junior high school students. based on the results, Micro-classes have the characteristics of short, compact and powerful, which can effectively help students with learning difficulties to learn and master mathematics efficiently within the effective learning time. Based on the characteristics of students with learning difficulties and micro-classes, the author explores the actual improvement effect of micro-classes on the mathematics learning of students with learning difficulties by designing micro-classes in a targeted manner and conducting comparative teaching experiments in the first two parallel classes.